2016
DOI: 10.1080/13657305.2016.1214629
|View full text |Cite
|
Sign up to set email alerts
|

Market integration between wild and farmed species in Spain

Abstract: Market integration occurs when prices among different locations or related goods follow similar patterns over time. Current knowledge on market integration between aquaculture and wild-caught fish is based on a small number of species and markets. Most studies show the existence of market integration between wild and farmed conspecifics, with the clear exception of European seabass and gilthead seabream in Southern European countries. In this study, we investigate whether this lack of market integration betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The lack of impact of the Chilean disease shock on price determination for salmon provides strong evidence of a highly integrated salmon market, where trade patterns shift to maintain the stable relative price. This is in contrast to some other markets for farmed fish, where fish size (Bjørndal and Guillen, 2017a; Regnier and Bayramoglu, 2017) or quality (Bjørndal and Guillen, 2017b; Norman-López and Asche, 2008; Pincinato and Asche, 2016; Rodríguez, Bande, and Villasante, 2013) segments the market. However, our results support and strengthen the general conclusion for most seafood markets—that for the same and similar species, there exist well-integrated markets (e.g., Ankamah-Yeboah, Stål, and Nielsen, 2017; Bronnmann, Ankamah-Yeboah, and Nielsen, 2016; Tveteras et al, 2012; Vinuya, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…The lack of impact of the Chilean disease shock on price determination for salmon provides strong evidence of a highly integrated salmon market, where trade patterns shift to maintain the stable relative price. This is in contrast to some other markets for farmed fish, where fish size (Bjørndal and Guillen, 2017a; Regnier and Bayramoglu, 2017) or quality (Bjørndal and Guillen, 2017b; Norman-López and Asche, 2008; Pincinato and Asche, 2016; Rodríguez, Bande, and Villasante, 2013) segments the market. However, our results support and strengthen the general conclusion for most seafood markets—that for the same and similar species, there exist well-integrated markets (e.g., Ankamah-Yeboah, Stål, and Nielsen, 2017; Bronnmann, Ankamah-Yeboah, and Nielsen, 2016; Tveteras et al, 2012; Vinuya, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…We fully recognize the limitations imposed by using a constant market price over time. Market prices of fish are known to vary according to supply and demand (Bjørndal and Guillen 2017), yet global analysis concluded that ex-vessel prices are relatively inelastic to supply and vice versa (Swartz et al 2013). Specifically, in the Mediterranean, variation in prices among commercial species is much larger than the variability in the price within the same species among years (Guillen and Maynou 2015) or among days of the week (Samy-Kamal et al 2015).…”
Section: Fishers' Revenuesmentioning
confidence: 99%
“…In addition, cultivated turbot lacks a clear substitute product that would generate competition affecting prices. Wild turbot is 120% more expensive and other fish products, such as seabream and seabass, are not clear substitutes for turbot either, as their prices are over 2€ lower (Bjørndal & Guillen, 2017). There are other flatfish on the market with organoleptic characteristics closer to turbot, such as sole, although their limited production volume means that they cannot function as substitutes for the moment.…”
Section: Resultsmentioning
confidence: 99%